Early Experience With the Clinical Use of Teprotumumab in a Heterogenous Thyroid Eye Disease Population - Diniz, Stefania B; Cohen, Liza M; Roelofs, Kelsey A; Rootman, Daniel B (Ophthalmic plastic and reconstructive surgery, 2021)
To describe the clinical course in a heterogeneous series of subjects with thyroid eye disease (TED) treated with teprotumumab. Cross-sectional cohort study including patients with clinical diagnosis of TED who was treated with teprotumumab. The entire cohort was analyzed together and subsequently in clinical subgroups based on stage and grade of disease. Primary outcome measure was change in proptosis ≥2 mm. Secondary outcome measures included change in clinical activity score (CAS), ductions, strabismic deviation, MRD1, and MRD2. Bivariate and multivariate statistics were performed. The study included 21 patients. Mean ± SD age was 61.5 ± 12.6 years and 71.4% were female. Reduction in proptosis ≥2 mm was achieved in 71.4% of the sample. Stage and grade were not significant predictors of outcome. Treatment with teprotumumab resulted in a 2.5 ± 1.8 mm reduction of proptosis (P < 0.001), 2.2 ± 1.4 reduction in CAS (P < 0.001), and 16.9 ± 19.3 degree improvement in extraocular motility (P < 0.001). There were no significant differences for change in CAS, proptosis, ductions, or MRD2 between different grades and stages of disease. Total strabismus and MRD1 improvement were greater in the active stage of disease (P < 0.05). Three cases of dysthyroid optic neuropathy, refractory to methylprednisolone therapy improved after initiation of teprotumumab. Treatment of TED with teprotumumab in a heterogeneous patient population is associated with improvement in proptosis, extraocular motility, and CAS. Patients beyond those defined in the clinical trials, including those affected by stable stage, milder grade, and vision-threatening TED may benefit from this therapy. There are, however, limits on the overall efficacy of this medication in the management of certain physical characteristics in TED including eyelid position and strabismus.